A new science of international relations modernity, complexity and the Kosovo conflict - Popolo, Damian (Routledge Ashgate Publishing, 2011)
Foucauldian methodology is here applied to Complexity Science in order to generate a new understanding of International Relations, particularly to the conflict in Kosovo. The book shows how theoretical issues inform understandings of crisis, leading to decisions in the real world of international policy-making.